Measurement of Value of Statistical Life by Evaluating Diarrhea Mortality Risk due to Water Pollution in Laos and Vietnam - Eiji Ohno; Masafumi Morisugi; Phouphet Kyophilavong; Hiroshi Sao (European Regional Science Association (ERSA), 2012)
Diarrhea mortality risk due to water pollution is one of serious problems that threaten human life in Asian developing countries. This study aims to provide basic data for the cost benefit analysis of countermeasures against diarrhea in Laos and Vietnam, and measures the value of statistical life (VSL) concerning diarrhea mortality risk by using the contingent valuation method (CVM). In this study, we have conducted interview survey in Laos and Vietnam in 2011 and 2010. The content of questionnaire sheet is to ask the willingness to pay (WTP) of residents to have a right to obtain improved water resources in their daily usages and avoid diarrhea mortality risk due to water pollution. By using the data set, we can know how much the residents want to pay for risk reduction, and know how much they evaluate their own life in monetary term, which is the VSL. Also, by summing up the WTP and comparing with the implementation cost, we can know whether or not they will agree to implement some policies or infrastructures. This kind of methodology, the CVM, is directly linked to context of cost-benefit analysis under uncertainty. The outputs of this study are our first attempt to approach the water resource conflict problem of Mekong River. It is apparent that consistent effort to find out certificate values of water resource for each region is urgent and necessary matter, and as an extension of it, we hope to collect the guideline at last to avoid such the worst catastrophic situation. As a result, we have derived the damage cost function of diarrhea, which includes the mortality risk change as its variable. By using the function, the WTP for reducing diarrhea mortality risk, where 20, 40, 60 and 80 persons will be saved every 100,000 population annually, has been measured 9.580, 11.131, 12.038 and 12.682 US per year in Laos and 41.932, 47.256, 50.371 and 52.581 US per year in Vietnam, respectively. And the VSL has been measured 47,898, 27,827, 20,064 and 15,853 US in Laos and 209,660, 118,141, 83,952 and 65,726 US in Vietnam, respectively.
Keywords: 330